Investigating normal stress effects on the shear and traction characteristics of performance infill materials used in artificial turf surfaces - McGowan, H.; Fleming, P.; James, D.; McMahon, J.; Pak, J.-H.; Forrester, S. (Sports Engineering, 2025)
Styrene butadiene rubber crumb is currently the most widely used performance infill material for artificial turf surfaces globally. Concerns about the impact of microplastics on the environment and human health has led to organic performance infill materials becoming more popular. Research surrounding these new performance infill materials is lacking; one key gap in knowledge is the relationship between normal stress and rotational traction. The purpose of this study was to analyse the relationship between normal stress and rotational traction for three performance infill materials: styrene butadiene rubber, cork and pine. Five normal stresses (10-46 kPa) were analysed during rotational traction testing on three artificial surface systems. Each performance infill material showed a positive, linear relationship between normal stress and mean peak torque, initial stiffness and secondary stiffness. However, the rate at which mean peak torque increased with normal stress varied between infilled systems. Pine infill increased at 1.55 Nm/kPa, cork at 1.51 Nm/kPa and styrene butadiene rubber at 1.16 Nm/kPa. Direct shear testing of each performance infill material was conducted at three normal stresses (25, 50 and 250 kPa) to investigate each performance infill materials relative resistance to shearing. The order of infill materials remained the same for both rotational traction and direct shear testing, with pine consistently producing the highest internal friction angle and styrene butadiene rubber the lowest. The results confirm the need to better understand the performance characteristics of organic infill materials used in artificial turf surfaces to maintain their safety and performance characteristics.